Enhancing treatment effects by combining continuous theta burst stimulation with smooth pursuit training. (July 2015) - Hopfner, Simone; Cazzoli, Dario; Müri, René M.; Nef, Tobias; Mosimann, Urs P.; Bohlhalter, Stephan; Vanbellingen, Tim; Nyffeler, Thomas
Abstract: Continuous theta burst stimulation (cTBS) represents a promising approach in the treatment of neglect syndrome. However, it is not known whether cTBS in conjunction with another technique may enhance the therapeutic effects. In the present sham-controlled study, we aimed to combine cTBS with smooth pursuit training (SPT), another method known to effectively improve neglect symptoms, and to evaluate whether this combination would result in a stronger effect than SPT alone. Eighteen patients with left spatial neglect after right-hemispheric stroke were included in the study and performed a cancellation task on a large 54.6″ touchscreen monitor. A sequential application of cTBS and SPT induced a significantly greater improvement of neglect than SPT alone. After the combined application of these two methods, patients detected significantly more targets and their cancellation behaviour presented a significantly greater shift towards the contralesional hemispace. We suggest that a combined, sequential application of cTBS and SPT is a promising new approach to treat neglect. Highlights: cTBS potentiates the effect of smooth pursuit training. cTBS sequentially combined with SPT has stronger effects than SPT alone. Patients significantly improved their cancellation behaviour. cTBS in conjunction with SPT is a promising combination in neglect therapy.